Phonetics Transcription in English Language Teaching (ELT): Implications for English Language Teachers - Teddy Fiktorius (NOTION: Journal of Linguistics, Literature, and Culture, 2020)
This paper is written through descriptive method or library research to discuss the use of phonetic transcription in the teaching of English as a foreign language (EFL) using the International Phonetic Alphabet (IPA). The first part describes the theoretical framework of the transcription basics. Then, the next part discusses the advantages of the phonetic transcription. This is followed by an illustration of understanding basic speech sounds. Some ideas of preparing classroom materials using the IPA are addressed in the next section. Finally, some solutions as well as recommendations are proposed and justification of the researcher’s position toward the use of phonics as an EFL literacy instruction in ELT is presented.